2012
DOI: 10.2118/136665-pa
|View full text |Cite
|
Sign up to set email alerts
|

Foamy-Oil-Viscosity Measurement

Abstract: Foamy-oil viscosity is a controversial topic among researchers regarding what happens to the oil viscosity when the solution gas starts coming out of solution because of decreasing pressure and the released gas starts migrating with the oil in the form of dispersed gas bubbles. For conventional oils, below the true bubblepoint pressure, the oil viscosity increases as the gas freely evolves from the oil. For foamy oils, it has been suggested that the apparent oil viscosity remains relatively constant or perhaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Dissolved gases (methane, ethane, carbon dioxide, nitrogen, etc.) are known to significantly reduce the viscosity of oils and bitumen by several orders of magnitude depending on the saturation pressure. Bergman and Sutton have also collected available data on gas-saturated oils (1850 samples) covering a limited viscosity range from 5 × 10 –5 to 3.3 Pa·s with GOR from 3 to 6500 scf/stb (0.5 to 1160 m 3 /m 3 ) and bubble pressure from 66 to 10300 psi (0.46 to 71.02 MPa), which they used for creation of an improved live-oil viscosity correlation. This comprehensive study demonstrates the absence of a live-oil viscosity correlation for heavy oils with higher viscosities, which can be used to predict their fluid transport characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolved gases (methane, ethane, carbon dioxide, nitrogen, etc.) are known to significantly reduce the viscosity of oils and bitumen by several orders of magnitude depending on the saturation pressure. Bergman and Sutton have also collected available data on gas-saturated oils (1850 samples) covering a limited viscosity range from 5 × 10 –5 to 3.3 Pa·s with GOR from 3 to 6500 scf/stb (0.5 to 1160 m 3 /m 3 ) and bubble pressure from 66 to 10300 psi (0.46 to 71.02 MPa), which they used for creation of an improved live-oil viscosity correlation. This comprehensive study demonstrates the absence of a live-oil viscosity correlation for heavy oils with higher viscosities, which can be used to predict their fluid transport characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…For foamy oils, it has been suggested that the apparent oil viscosity remains relatively constant or perhaps declines slightly between the true bubblepoint and a characteristic lower pressure, called pseudo-bubblepoint, which is the pressure at which the gas starts separating from the oil. Below this pressure, the viscosity increases, reaching the dead-oil value at atmospheric pressure [15] Parallel solution gas drive experiments were conducted with a heavy crude oil from reservoir and a deasphalted version of the same oil and to eliminate the influence of oil viscosity, the original crude oil was diluted with a 50-50 mixture of heptane and toluene to reduce the viscosity to the same level as that of the deasphalted oil. The experiments were carried out in a visual sand pack that permitted observation of the bubble formation in the sand.…”
Section: Viscositymentioning
confidence: 99%
“…Since pressure has little impact on either the liquid viscosity (Alshmakhy and Maini, 2012;Freitas et al, 2014;Yan et al, 2014) or liquid density (Abdulagatov et al, 2014;Hussein and Amin, 2010), oil, water, and their mixture are considered as Newtonian and incompressible fluids. And there is no heat exchange or work between the fluid and environment, the system remains isothermal.…”
Section: Modelingmentioning
confidence: 99%